Phenolic Contents and Antioxidants Activities in Jamman Fruit (Eugenia jambolana) Products - Sheikh, Saghir Ahmed; Shahnawaz, Muhammad; Nizamani, Shafi Muhammad; Bhanger, Muhammad Iqbal; Ahmed, Ejaz (Journal of Pharmacy and Nutrition Sciences, 2022)
In this study, total phenolic contents and antioxidant activity were determined in various products made from two cultivars of jamman fruit (Eugenia jambolana) i.e. improved (V1) and indigenous (V2). Five products were made from each cultivar such as jam, squash, ready-to-drink juice, pulp powder and seed powder. Fruit cultivars were endogenous to the typical region of Sindh-Pakistan. Total phenolic contents were analyzed by Folin-Ciocalteu colorimetric method, whereas, the total antioxidant activity was analyzed by using the 2, 2-diphenil-1-picrylhydrazyl radical scavenging capacity (DPPH) assays. The highest total phenolic contents and antioxidants were observed in freeze dried seed powder while the lowest contents were found in squash.